Influence of Precursor Type on Activated Carbon Prepared by Phosphoric Acid-Chemical Activation for Supercapacitor Applications - Bhandari, Sujan; Rajguru, Kirti B.; Gnawali, Chhabi L.; Pokharel, Bhadra P. (Journal of Nepal Physical Society, 2023)
Phosphoric acid can be used to activate different precursors and produce activated carbon (AC), a porous material with high adsorption capacity and surface area. This research shows how AC is made using different locally available precursors, namely amla seeds and harro seeds. We compare how the carbonization temperature and the precursor type affect the surface area, pore structure, and electrochemical properties of the AC. We use different methods to analyze the AC samples, such as scanning electron microscopy, surface area, methylene blue number, iodine number, and cyclic voltammetry. We show that the best conditions for making AC depend on the type of precursor and the activation temperature.